How to Search for Life in Martian Chemical Sediments and Their Fluid and Solid Inclusions Using Petrographic and Spectroscopic Methods - Benison, Kathleen C. (Frontiers in Environmental Science, 2019)
Abundant resources and efforts have been employed in the search for life on Mars. Satellites, landers, and rovers have tested atmospheric gases, general sediment and rock compositions, and images of Mars surface in an effort to detect biosignatures left by any possible modern or ancient life. Chloride and sulfate minerals suggestive of past acid saline lakes have been found on Mars. In some terrestrial acid brine environments, these minerals trap microorganisms and organic compounds and preserve them for long geologic time periods within fluid inclusions and as solid inclusions. Some cells remain viable, especially in the isolated, microscopic aqueous environments of fluid inclusions. Fluid inclusions in these same saline minerals on Mars have yet to be examined. This paper describes petrographic and geochemical methods that have been used recently to detect and make general identifications of microorganisms and organic compounds preserved in modern and Permian Mars-analog acid saline lake halite and gypsum. It then makes recommendations for how martian chemical sediments could be examined for these biosignatures, both by rovers and in returned samples. This new protocol for the examination of martian chemical sediments and sedimentary rocks may provide the best way to identify any preserved biosignatures on Mars.